A method for predicting maximal strength in collegiate women athletes - Horvat, M.; Ramsey, V.; Franklin, C.; Gavin, C.; Palumbo, T.; Glass, L. A. (The Journal of Strength and Conditioning Research, 2003)
The purpose of this study was to develop a regression equation capable of accurately predicting a 1 repetition maximum bench press in collegiate women athletes. The findings of this study could benefit future women athletes by providing coaches and trainers with an easy method of determining maximum upper body strength in women athletes. Sixty-five University of Georgia NCAA Division 1 women athletes from 9 different sports were measured prior to the start of their season utilizing 2 repetition tests to fatigue (25 kg: REPS55; 31.8 kg: REPS70) and a 1 repetition maximum (1RM) bench press test in random order. Other independent variables that were used with a submaximal weight to predict 1RM were total body weight, lean body mass (LBM), height, and percent body fat. The variables of REPS70 and LBM were the best predictors of 1RM utilizing Pearson product correlations (r = 0.909, p = 0.000; r = 0.445, p = 0.000) and multiple regression results (R2 = 0.834, p = 0.000) for this population. The results from this study indicate muscular endurance repetitions using an absolute weight of 31.8 kg in conjunction with LBM can be used to accurately predict 1RM bench press strength in collegiate women athletes.